Psychometric validation of the Female Sexual Distress Scale-Desire/Arousal/Orgasm - Leonard R. Derogatis; Dennis A. Revicki; Raymond C. Rosen; Robert Jordan; Johna Lucas; Carl Spana (SpringerOpen, 2021)
Abstract Background For the treatment of female sexual dysfunction, the most relevant outcome measures are patient-reported treatment effects and changes in symptoms, underscoring the need for reliable, validated patient-reported outcome (PRO) instruments. The aim of this study was to evaluate the psychometric characteristics (validity and reliability) of the Female Sexual Distress Scale-Desire/Arousal/Orgasm (FSDS-DAO) PRO measure, which was adapted from the validated FSDS-Revised (FSDS-R) questionnaire and added 2 questions involving arousal and orgasm. Methods Psychometric analyses were based on the data from a multicenter phase 2b dose-finding study that compared the safety and efficacy of bremelanotide versus placebo and were conducted in the evaluable modified intent-to-treat population (N = 325) from that study. Psychometric evaluation of the new items in the FSDS-DAO included confirmatory factor analyses, tests of internal consistency and test-retest reliability, examinations of convergent and discriminant validity, and determination of responsiveness. The validity of the FSDS-DAO was evaluated based on previously developed instruments, including the Female Sexual Function Index (FSFI), General Assessment Questionnaire (GAQ), Women's Inventory of Treatment Satisfaction (WITS-9), and Female Sexual Encounter Profile-Revised (FSEP-R). Results Confirmatory factor analyses demonstrated that the FSDS-DAO items fit very well (Bentler's comparative fit index of 0.929). Cronbach's α for the FSDS-DAO total score was ≥ 0.91 at Visits 1, 2, 5, and 12, demonstrating adequate internal consistency reliability. Test-retest reliability was acceptable with an intra-class coefficient of 0.61 and a Spearman's correlation coefficient score of 0.62 between Visits 1 and 2 (4 weeks). Acceptable construct validity was demonstrated by significant correlations with related PRO scales in the expected directions and magnitude. For example, participants reporting the worst levels of sexual function on the FSFI also showed the worst FSDS-DAO scores at Visits 5 and 12. The FSDS-DAO total score was responsive to change. Conclusions Evidence supports the validity and reliability of the FSDS-DAO for assessing sexually related distress in women with female sexual arousal disorder and/or hypoactive sexual desire disorder; the addition of the arousal and orgasm items did not impact the validity and reliability of the measure. Clinical Trial Registration ClinicalTrials.gov NCT01382719.